SKRINING FITOKIMIA DAN KARAKTERISTIK FISIK SAMPO EKSTRAK KULIT BUAH RENGGAK (Ammomum Dealbatum Roxb.) - Hawani Sahira; Dewi Yuliana Rizqi; Jihan Maftuuhatus Zhura; Lalu Rizki Fauzi (Fakultas Farmasi Universitas Muslim Nusantara Al Washliyah, 2026)
The peel of Renggak fruit (Amomum dealbatum Roxb.) has been shown to contain bioactive metabolites with potential as active ingredients in shampoo formulations. This study aims to conduct phytochemical screening and evaluate the physical characteristics of a shampoo formulation containing Renggak peel extract. Extraction was performed by maceration using 96% ethanol as the solvent. Ethanol extract was incorporated into the shampoo formulations at final extract concentrations of 1.1% (F1), 1.65% (F2), and 2.2% (F3), based on the total formulation mass. Phytochemical screening was based on the identification of alkaloids, flavonoids, and saponins. The physical characteristics tests included organoleptic evaluation, pH, viscosity, and foam height. The results showed that the ethanol extract of Renggak peel contains alkaloids, flavonoids, and saponins. In addition, the physical characteristics tests indicated that all three formulations had good organoleptic properties, and their pH, viscosity, and foam height were within the standard range for shampoo preparations. Based on the results, it can be concluded that Renggak fruit peel extract has the potential to be formulated into a shampoo preparation with good physical characteristics and in accordance with shampoo quality standards. Keywords: Shampoo, Renggak peel extract, phytochemical screening, physical characteristics